(untitled) (Ius Novum, 2019)
Expropriation of real estate is connected with the necessity to pay compensation. Such a necessity results directly from Article 21 para. 1 of the Constitution of the Republic of Poland, which stipulates that expropriation may be allowed solely for public purposes and for just compensation. The concept of just compensation has not been normatively defined. The binding regulations stipulate the rules and procedure of determining compensation. In its basic scope, it is a solution adopted in law before the changes of the social and political system took place after 1989, i.e. before the Constitution of the Republic of Poland entered into force. In this context, there are many theoretical and practical problems connected with defining the amount of compensation, and first of all, its scope. In other words, legal regulations do not explicitly resolve the issue whether just compensation is only the one which covers the actual, real loss, thus a market value of the real estate, or the one which includes lost profits, i.e. the profits that the property title would gain in future if it was within the area of the influence of the given entity. In jurisprudence and jurisdiction no clear solution to this problem was offered, thus the article deals with this aspect, indicating the imperfections and insufficiency of the existing special regulation evaluated from the perspective of the principles defined in the Constitution. The basic assumption presented on the basis of the considerations of the law in force is that just compensation as a condition for expropriation should also take into account the right level of protection of the real estate ownership, which can take place only if such ownership has actual economic significance.